2019
DOI: 10.1002/tesj.450
|View full text |Cite
|
Sign up to set email alerts
|

A dialogic approach to exploring culture in community‐based adult ESL classrooms

Abstract: Despite the robust literature about teaching intercultural competence, little has been written on exploring culture in community‐based English as a second language (ESL) settings, such as classes for adults with immigrant and refugee backgrounds. Educational materials about culture designed for these contexts tend to be prescriptive and essentializing, displaying rules and norms without inviting dialogue or accounting for variation. This article addresses this gap by dialogically exploring perceptions of adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Addressing the democracy and inclusion purpose of lifelong learning, instructors should frame cultural conversations regarding legal issues and social norms as well as the learners' rights to safety, freedom of expression, gender equality, and respect, rather than imposing the culture of the host country dominantly (Shufflebarger Snell, 2020). To minimize the problems of access and increase participation, instructional communication technologies should be tailored towards adult refugee language and culture learning needs, used as supplementary resources, or the primary source of instruction when necessary.…”
Section: Best Teaching Practicesmentioning
confidence: 99%
“…Addressing the democracy and inclusion purpose of lifelong learning, instructors should frame cultural conversations regarding legal issues and social norms as well as the learners' rights to safety, freedom of expression, gender equality, and respect, rather than imposing the culture of the host country dominantly (Shufflebarger Snell, 2020). To minimize the problems of access and increase participation, instructional communication technologies should be tailored towards adult refugee language and culture learning needs, used as supplementary resources, or the primary source of instruction when necessary.…”
Section: Best Teaching Practicesmentioning
confidence: 99%
“…Extensive research has reported students' and teachers' development of interculturality through telecollaboration projects and experiences abroad (Dressler & Tweedie, 2016; Medina‐López‐Portillo, 2013; Olaya & Gómez, 2013). Another research line has explored the methodologies and, more recently, the practices teachers use to foster interculturality in the high school and college language curriculum (Byram & Kramsch, 2008; Crozet & Díaz, 2020; Díaz, 2013; Kearney, 2021; Kohler, 2020; Kramsch, 2011; Menard‐Warwick, 2009; Wagner et al., 2018) as well as community‐based refugee communities (Shufflebarger Snell, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…. Another research line has explored the methodologies and, more recently, the practices teachers use to foster interculturality in the high school and college language curriculum (Byram & Kramsch, 2008;Crozet & Díaz, 2020;Díaz, 2013;Kearney, 2021;Kohler, 2020;Kramsch, 2011;Menard-Warwick, 2009;Wagner et al, 2018) as well as community-based refugee communities (Shufflebarger Snell, 2019).…”
mentioning
confidence: 99%